Determination of elements level in sheep milk from two regions of Slovakia and health risk assessment of its consumption - Almášiová, Simona; Toman, Róbert; Pšenková, Martina; Tančin, Vladimir; Jančo, Ivona (Animal welfare, Ethology and Housing Systems (AWETH), 2023)
Milk as a nutritional dense component of diet plays a tremendous role in building a healthy society. However, due to environmental pollution, milk can contain heavy metals and trace elements as well which can threaten human health. The objective of this study was to determine and compare the content of 22 elements (Ag, Al, As, Ba, Ca, Cd, Co, Cr, Cu, Fe, K, Li, Mg, Mn, Mo, Na, Ni, Pb, Sb, Se, Sr, Zn) in raw sheep milk collected from the area with potentially undisturbed environment (region Stredné Považie) and area with the heavily disturbed environment (region Spiš) in Slovakia. Analysis of the elements was determined using an inductively coupled plasma-optical emission spectrometer with axial plasma configuration and with auto-sampler SPS-3. Concentrations of only 8 elements (Ca, Na, K, Mg, Al, Fe, Li, and Zn) were found above the detection limit in samples from the potentially undisturbed area, while a whole range of elements was found in samples from the area with heavily disturbed region except three elements (Ag, Cd, and Co) which were below the limit of detection. Significantly higher (P < 0.05) concentrations of Na, K, and Zn were found in the Spiš region. The highest concentration of four essential elements Ca, K, Mg, Na, and toxic element Al in samples of sheep milk was found. The hazard index (HI) values were higher than 1 in samples from both monitored farms (6.57 from the farm in the Spiš region and 4.95 in the Stredné Považie region). The highest target hazard quotient (THQ) represents the presence of Al (3.95 and 4.92) in both regions and As (2.17) in the Spiš region. THQ of other monitored elements was less than 1, which means these elements would unlikely cause adverse health effects. Our results indicate that exclusive and long-term consumption of milk from spotted farms can potentially lead to adverse non-carcinogenic health effects due to regular intake of heavy metals, especially Al and As, which can be hazardous mainly for risky groups.